Stomatal Size, Stomatal Frequency and Pollen Grain Diameter as Indirect Method for Identification of Ploidy Levels in Cotton - Arunee Wongpiyasatid; Praparat Hormchan; Katarut Chusreeaeom; Ngamchuen Ratanadilok (Agriculture and Natural Resources, 2005)
Seeds of diploid local variety cotton (Gossypium arboreum), PM2, were treated with 0, 0.1 and 0.5% colchicine solutions at duration of 24 and 36 hours for polyploidy induction. Seed germination, seedling survival, stomatal size, stomatal frequency, percent pollen grain sterility and pollen grain diameter were recorded. The results showed seed germination, seedling survial and stomatal frequency to be negatively correlated with colchicine concentrations and durations of seed soaking while numbers of plant having large stomatal size and % pollen grain sterility have positive correlation. Stomatal size increased whereas stomatal frequency decreased. No correlation between pollen grain diameter and colchicine concentrations as well as durations of seed soaking was found.